Carotenoids: Therapeutic strategy in the battle against viral emerging diseases, COVID-19: An overview - Khalil, A. А.; Tazeddinova, D.; Aljoumaa, K.; Kazhmukhanbetkyzy, Z. A.; Orazov, A.; Toshev, A. D. (Preventive Nutrition and Food Science. - 2021, 2021)
Carotenoids, a group of phytochemicals, are naturally found in the Plant kingdom, particularly in fruits, vegetables, and algae. There are more than 600 types of carotenoids, some of which are thought to prevent disease, mainly through their antioxidant properties. Carotenoids exhibit several biological and pharmaceutical benefits, such as anti-inflammatory, anti-cancer, and immunity booster properties, particularly as some carotenoids can be converted into vitamin A in the body. However, humans cannot synthesize carotenoids and need to obtain them from their diets or via supplementation. The emerging zoonotic virus severe acute respiratory syndrome coronavirus 2, which causes coronavirus disease 2019 (COVID-19), originated in bats, and was transmitted to humans. COVID-19 continues to cause devastating international health problems worldwide. Therefore, natural preventive therapeutic strategies from bioactive compounds, such as carotenoids, should be appraised for strengthening physiological functions against emerging viruses. This review summarizes the most important carotenoids for human health and enhancing immunity, and their potential role in COVID-19 and its related symptoms. In conclusion, promising roles of carotenoids as treatments against emerging disease and related symptoms are highlighted, most of which have been heavily premeditated in studies conducted on several viral infections, including COVID-19. Further in vitro and in vivo research is required before carotenoids can be considered as potent drugs against such emerging diseases. Каротиноиды, группа фитохимических веществ, естественным образом встречаются в царстве растений, особенно во фруктах, овощах и водорослях. Существует более 600 видов каротиноидов, некоторые из которых, как считается, предотвращают болезни, в основном благодаря своим антиоксидантным свойствам. Каротиноиды проявляют несколько биологических и фармацевтических преимуществ, таких как противовоспалительные, противораковые и укрепляющие иммунитет свойства, в частности, поскольку некоторые каротиноиды могут превращаться в витамин А в организме. Однако люди не могут синтезировать каротиноиды и должны получать их из своего рациона или в виде добавок. Возникающий зоонозный вирус тяжелого острого респираторного синдрома коронавирус 2, вызывающий коронавирусную болезнь 2019 (COVID-19), возник у летучих мышей и передался людям. COVID-19 продолжает вызывать серьезные проблемы со здоровьем во всем мире. Следовательно, следует оценивать естественные профилактические терапевтические стратегии с использованием биологически активных соединений, таких как каротиноиды, для усиления физиологических функций против появляющихся вирусов. В этом обзоре обобщены наиболее важные каротиноиды для здоровья человека и повышения иммунитета, а также их потенциальная роль в развитии COVID-19 и связанных с ним симптомов. В заключение подчеркивается многообещающая роль каротиноидов в лечении возникающих заболеваний и связанных с ними симптомов, большинство из которых были тщательно продуманы в исследованиях, проведенных на нескольких вирусных инфекциях, включая COVID-19. Необходимы дальнейшие исследования in vitro и in vivo, прежде чем каротиноиды можно будет рассматривать как сильнодействующие лекарства против таких возникающих заболеваний.
Keywords: скопус; импакт-фактор 2021; научный журнал; зарубежное издание; периодическое издание; дальнее зарубежье; зарубежные авторы; каротиноиды; лекарственные растения; вирусные инфекции; лечение вирусных заболеваний